Karakteristik Fisik dan Penyimpanan Bahan Baku Teh Herbal Healing Tea di PT. Karsa Abadi (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2023)
This study is an exploratory research with the aim of determining the physical characteristics and storage of raw materials for Healing Tea herbal tea at PT. Karsa Abadi. The raw materials of this herbal tea are gemitir flowers, knob flowers, rose flowers, and citronella leaves. The research methods used are the RHS color chart in the raw material inventory process (sortation), the gravimetric method for checking moisture content in the raw material drying process, and the FIFO (First In First Out) method in the raw material storage process. The results showed the color intensity of wet raw materials, among others: gemitir flowers L(77,9), a*(8,2), and b*(78,6); knob flowers L(38,8), a*(68,5), and b*(-29,1); roses L(41,8), a*(68,5), and b*(11,0); and citronella leaves L(65,3), a*(-17,3), and b*(36,0). Then, the color intensity of dry raw materials includes: gemitir flowers L(47.8), a*(29.6), and b*(55.3); knob flowers L(22,6), a*(47,9), and b*(-22,3); roses L(25,3), a*(34,2), and b*(-13,5); and citronella leaves L(51,7), a*(-0,2), and b*(26,5). The moisture content of dry raw materials is gemitir flowers (7.45%), knob flowers (7,55%), roses (7,89%), and citronella leaves (7,23%). Meanwhile, the process of storing raw materials is used in and out of one direction. The conclusion of this study is that the physical characteristics of the color of wet raw materials and dry raw materials of Healing Tea herbal tea are good and according to company criteria, the moisture content of each dry raw material is
Keywords: teh herbal; Healing Tea; fisik; penyimpanan; PT. Karsa Abadi